Pyranoxanthones from Mesua ferrea - Teh, Soek Sin; Ee, Gwendoline Cheng Lian; Rahmani, Mawardi; Yap, Taufiq Yun Hin; Go, Rusea; Mah, Siau Hui (MDPI, 2011)
Our phytochemical studies on the root bark extracts of Mesua ferrea have led to the isolation of two new pyranoxanthones, mesuaferrin A (1) and mesuaferrin B (2). Five other compounds – caloxanthone C (3), 1,8-dihydro-3-methoxy-6-methylanthraquinone (4), β-sitosterol (5), friedelin (6) and betulinic acid (7) – were also successfully isolated. Structural elucidations of these compounds were achieved using 1D and 2D NMR and MS techniques.